(3GdQSGdI GdJi oCQSdJ Edi hdi GdYgO (B( (3YgO GdeSdejf YHO GdQMje Hf EdjGS (B)s
(3ChdgG (B:s
(3JhcdJ Ydi CejQ GdeDefjf Ld PcQg hHg GSJYjf ai LejY GdGehQ ef YHO CejQ GdeDefjf Edi GdYgO YgO GdeSdejf hNdjaI CejQ GdeDefjf GeG HYO abO MGf dhdi GdYgO Cf jcTa GdbfGY s
(3BNQgG (B:s
(3hbO CYPQ GdgGOi hfGOi GdefGOi heG Ydi GdQShd EdG GdHdGZ GdeHjf JeJ GdQSGdI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B12s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV cdeGJgG HGdMeQIs
(3QSGdI ef QSGFd GdOQhR s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds